IDENTIFICATION OF NEW ADVANCED GLYCATION END PRODUCTS INHIBITORS: DEVELOPMENT OF A 96-WELL PLATE SCREENING - Chaigneau, A.; Richomme, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The non-enzymatic Maillard reaction is divided into two stages. The early one consists in the formation of a Schiff base between the amino group of a protein and the aldehyde group of a reducing sugar which then evolves into an Amadori rearrangement product. The later one involves several processes: complicated oxidation reaction, dehydrogenation and condensation followed by formation of fluorescent proteins through the so-called Advanced Glycation End Products (AGEs). This glycation of proteins causes structural as well as functional changes. Indeed, the accumulation of AGEs may contribute to the pathogenesis of diabetes, neurological diseases or vascular disorders. AGEs also play a predominant role in cellular aging. Therefore AGEs inhibitors and breakers (AGEIB) not only represent potential therapeutics for the aforementioned diseases1,2 but can also be used in the formulation of new food supplements or innovative cosmetics. In this aim a new 96-well plate screening of AGEIB was developed in our laboratory. The efficiency of this test will be discussed and illustrated by many examples dealing with natural products (crude plant extracts, secondary metabolites, structural analogues). Besides, in order to study specific inhibitors of the last and irreversible steps of the formation of AGEs, several improvements of this evaluation will be proposed.